2021
DOI: 10.1103/physrevb.103.134406
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order of Dy3+ and Fe3+ moments in antiferromagnetic Dy

Abstract: We report on spin Hall magnetoresistance (SMR) and spin Seebeck effect (SSE) in a single crystal of the rare-earth antiferromagnet DyFeO 3 with a thin Pt film contact. The angular shape and symmetry of the SMR at elevated temperatures reflect the antiferromagnetic order of the Fe 3+ moments as governed by the Zeeman energy, the magnetocrystalline anisotropy, and the Dzyaloshinskii-Moriya interaction. We interpret the observed linear dependence of the signal on the magnetic field strength as evidence for field-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
(94 reference statements)
0
8
1
Order By: Relevance
“…More important than the knowledge about the presence or absence of an F-type coupling is the information that it would be allowed within the same IR. This is different from the magnetic order as supposed in the recent literature [7,8,18,20,21,24,25] for the Dy-sublattice with k = 0 and the Γ 5 (G x A y ) model which has no third allowed BV. Figure 5 displays the refinement of the T = 1.6 K data ignoring BV3 but including a small contribution from the third harmonics of the k = [0, 0, l] phase (see figure 4 for the (001) +3k reflection).…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…More important than the knowledge about the presence or absence of an F-type coupling is the information that it would be allowed within the same IR. This is different from the magnetic order as supposed in the recent literature [7,8,18,20,21,24,25] for the Dy-sublattice with k = 0 and the Γ 5 (G x A y ) model which has no third allowed BV. Figure 5 displays the refinement of the T = 1.6 K data ignoring BV3 but including a small contribution from the third harmonics of the k = [0, 0, l] phase (see figure 4 for the (001) +3k reflection).…”
Section: Resultscontrasting
confidence: 81%
“…The possibility to recover the Γ 4 groundstate in DyFeO 3 applying an external magnetic field even below T SR has been first shown by Belov et al [16] and further discussed by Eremenko et al [17] and later again by Tokunaga et al [18]. While the value of T SR has been given as lying between 30 K and 52 K [1,8,[18][19][20] from magnetization, spin Hall magnetoresistance and neutron diffraction studies using single crystals, Rajeswaran et al [21] found the onset of T SR at 80 K from Mössbauer and magnetization studies on a powder.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…SMR has been observed in paramagnetic CoCr 2 O 4 [10], amorphous yttrium iron garnet (YIG) [11], Cr 2 O 3 [12], NdGaO 3 [13], and gadolinium gallium garnet (GGG) [14]. The SMR revealed magnetic phase transitions in α-Fe 2 O 3 [15], CoCr 2 O 4 [10], and DyFeO 3 [16] and magnetic domain structures [17]. The SMR in the longitudinal resistance of a metal contact on an antiferromagnet with two sublattices A and B reads…”
Section: Introductionmentioning
confidence: 98%
“…The SMR revealed magnetic phase transitions in α-Fe 2 O 3 [75], and DyFeO 3 2.4. MAGNETORESISTANCE 2 23 [76] and magnetic domain structures [77].…”
Section: Spin Hall Magnetoresistancementioning
confidence: 99%